Assessing marine biosecurity risks when data are limited: bioregion pathway and species-based exposure analyses. (23rd December 2014) - Azmi, Fauziah; Primo, Carmen; Hewitt, Chad L.; Campbell, Marnie L.
Abstract: We evaluated two risk models (bioregion pathway and species-based exposure), with the aim to determine an effective strategy to implement marine biosecurity risk management in regions/countries where biological data are limited. We used the Port of Tanjung Priok, Jakarta Bay, Indonesia, as a case study to test both models. The bioregion pathway model illustrates that Tanjung Priok is highly connected to the East Asian Sea (∼91%), and the Northwest Pacific, Mediterranean, and Australia & New Zealand bioregions ("Very Low" risk), with other bioregions posing "Negligible" risk, highlighting the importance of understanding regional port linkages. The bioregion pathway model strength is grounded by using readily available shipping data; however, it does not classify species into threat categories but considers a larger number of species as an increasing threat. The species exposure model found that 51 species pose a theoretical risk (10 "Moderate", 20 "High", and 21 "Extreme" risks) to Tanjung Priok. These 51 species can be used as a "watch list" for this port. If biosecurity measures for this port were restricted to the outcomes of the bioregion pathway model only 4 of the 51 species highlighted by the species exposure model would have been captured. The species model was data intensive, requiring extensive species datasets and consequently may be unsuitable when data are limited.